2014
DOI: 10.1001/jamapediatrics.2013.5488
|View full text |Cite|
|
Sign up to set email alerts
|

Electronic Cigarettes and Conventional Cigarette Use Among US Adolescents

Abstract: Importance E-cigarette use is increasing rapidly among adolescents and e-cigarettes are currently unregulated. Objective Examine e-cigarette use and conventional cigarette smoking. Design Cross-sectional analyses of survey data. Setting 2011 and 2012 National Youth Tobacco Surveys (NYTS) Participants Representative sample of US middle and high school students in 2011 (n=17,353) and 2012 (n=22,529) Exposures Ever and current e-cigarette use Main outcome measures Experimentation with, ever, and curre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

37
361
7
11

Year Published

2014
2014
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 463 publications
(416 citation statements)
references
References 33 publications
37
361
7
11
Order By: Relevance
“…In fact in the 2014 survey, virtually all teenagers (99%) who had never smoked cigarettes had also never tried e-cigarettes. This reflects trends across similar studies in other parts of the UK (ASH Scotland, 2014;ASH, 2015b;Public Health England, 2015) and indeed in the US (CDC, 2013;Dutra and Glantz, 2014). A separate national study of English 15 year olds in 2014 found that whilst 18% had tried e-cigarettes at least once only 3% currently used them (Ipsos MORI, 2015).…”
Section: Introductionmentioning
confidence: 78%
“…In fact in the 2014 survey, virtually all teenagers (99%) who had never smoked cigarettes had also never tried e-cigarettes. This reflects trends across similar studies in other parts of the UK (ASH Scotland, 2014;ASH, 2015b;Public Health England, 2015) and indeed in the US (CDC, 2013;Dutra and Glantz, 2014). A separate national study of English 15 year olds in 2014 found that whilst 18% had tried e-cigarettes at least once only 3% currently used them (Ipsos MORI, 2015).…”
Section: Introductionmentioning
confidence: 78%
“…Recent research suggests that the use of e-cigarettes may encourage, rather than discourage, the use of conventional cigarettes among US adolescents. 92,93 A new approach to aid in tobacco cessation is the use of an antiaddiction vaccine that will induce antibodies that block the pharmacologic effects of nicotine. 94 Nicotine is nonimmunogenic and must be conjugated as a hapten to a protein carrier.…”
Section: Cessationmentioning
confidence: 99%
“…Similarly, although we did not have a specific hypothesis about flavors, we were interested in exploring if use of menthol and sweet flavors differed among smokers, who presumably may have had more experience with flavors in tobacco products, when compared with nonsmokers. Finally, considering the unrestricted vigorous marketing of these devices in ways that are prohibited for cigarettes 15 and the established strong influences of both advertising 16 and exposure to other smokers like parents 17 and peers 18 on adolescent cigarette use behaviors, we also explored where adolescents had observed e-cigarette marketing and where they acquired their e-cigarettes.…”
Section: E-cigarette Use Among High School and Middle School Adolescementioning
confidence: 99%